Effect of feeding canola meal to laying Japanese quails - Priscila de Oliveira Moraes; Edenilse Gopinger; Aiane Aparecida Catalan; Martha Lopes Schuch de Castro; Moacir Cardoso Elias; Eduardo Gonçalves Xavier (Acta Scientiarum. Animal Sciences, 2015)
This study evaluated the effect of different levels of canola meal in the diet to laying Japanese quails on productive performance, egg quality and economic viability. A total of 120 80-day-old Japanese quails (Coturnix coturnix japonica) with average weight 146.54 ± 12 g were evaluated during 84 days. Dietary treatments consisted of the replacement of soybean meal with canola meal at 0, 10, 20, 30, 40 or 50%. We evaluated economic viability, productive performance, internal and external quality of eggs. Data were analyzed by polynomial regression at 5%. Body weight decreased linearly as the level of canola meal increased (p = 0.0055). Egg weight (p = 0.0032) and diameter (p = 0.0398) showed a quadratic response, increasing up to 30% substitution with subsequent reduction. Yolk color increased linearly as the level of canola meal increased (p = 0.0039). Canola meal can substitute soybean meal up to 30% without impairing productive performance, egg quality and diet cost.